Preparation method of modified natural ester insulating oil based on KH550 surface modification nanoparticles

By mixing the nano-TiO2 modified with KH550 surface with natural ester insulating oil, the problems of high dielectric loss and poor oxidation stability of natural ester insulating oil are solved, and the high electrical performance and long service life of modified natural ester insulating oil are achieved.

CN119570549AActive Publication Date: 2025-03-07ELECTRIC POWER RES INST CHINA SOUTHERN POWER GRID CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411860531.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-07
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Natural ester insulating oil has high dielectric loss and poor oxidation stability, which limits its wide application and service life in power systems.

Method used

Modified natural ester insulating oil is prepared by mixing KH550 surface modified nano-TiO2 with natural ester insulating oil to improve its electrical properties and physical and chemical properties.

Benefits of technology

Modified natural ester insulating oil exhibits high breakdown voltage, low dielectric loss, stable electric field bearing capacity and extended service life, significantly improving its aging resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570549A_ABST
    Figure CN119570549A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of insulating oil, and particularly discloses a preparation method of modified natural ester insulating oil based on KH550 surface modified nanoparticles, and the modified natural ester insulating oil is finally obtained by mixing the KH550 surface modified nanoparticles with a base solution containing VR100 rapeseed-based insulating oil and PFAE insulating oil. The KH550 surface modified nano particle modified natural ester insulating oil has the characteristics of high breakdown voltage, low dielectric loss and low volume resistivity, and the advantage of the modified natural ester insulating oil is still stable after entering an aging stage. Compared with the prior art, the modified natural ester insulating oil based on KH550 surface modification nanoparticles shows stronger aging resistance, can precisely meet diversified requirements of electrical equipment, greatly prolongs the service life of the equipment, and solves the problems of high dielectric loss and poor oxidation stability of the existing natural ester insulating oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of insulating oils, and in particular to a method for preparing natural ester insulating oil modified by KH550 surface-modified nanoparticles. Background Art

[0002] With the advancement of the construction of a strong green power grid and the deepening of the trend of clean and low-carbon energy transformation, traditional mineral insulating oils have been unable to meet the stringent requirements of transformers and other power equipment for liquid insulating media due to their inherent characteristics. Natural ester insulating oils are derived from vegetable oils, which have significant advantages such as high ignition point, high flash point, high electrical strength and easy degradation, demonstrating the characteristics of green, environmentally friendly and renewable resources.

[0003] However, the chemical composition of natural ester insulating oil is dominated by long-chain macromolecular triglycerides, which makes it have a high viscosity. Since transformers mainly rely on convection heat transfer to achieve heat transfer, high-viscosity natural ester insulating oil forms an obstacle in the heat exchange process, which is not conducive to the efficient dissipation of heat and easily causes the transformer operating temperature to rise, thereby limiting the service life of the transformer and even inducing transformer failure in severe cases.

[0004] In addition, compared with mineral insulating oil, natural ester insulating oil performs poorly in terms of oxidation stability and has relatively high dielectric loss. These unfavorable factors have, to a considerable extent, hindered the widespread promotion and application of natural ester insulating oil in the field of power systems. In view of this, the development of a natural ester insulating oil that can exhibit good characteristics in both electrical performance and physical and chemical properties has a critical significance and far-reaching value that cannot be ignored in driving the industry towards a low-carbon transformation path and assisting the construction of a green and strong power grid. Summary of the invention

[0005] In view of this, the purpose of the present application is to provide a method for preparing natural ester insulating oil modified by KH550 surface-modified nanoparticles, so as to solve the problems of high dielectric loss and poor oxidation stability of existing natural ester insulating oil.

[0006] In order to achieve the above technical objectives, the present application provides a method for preparing natural ester insulating oil modified by KH550 surface-modified nanoparticles, which is as follows:

[0007] The KH550 surface modified nanoparticles are uniformly mixed with natural ester insulating oil to obtain modified natural ester insulating oil.

[0008] Further, the natural ester insulating oil includes VR100 rapeseed-based insulating oil and PFAE insulating oil.

[0009] Furthermore, the natural ester insulating oil includes VR100 rapeseed-based insulating oil and PFAE insulating oil, and the mass ratio of VR100 rapeseed-based insulating oil to PFAE insulating oil is 4:1.

[0010] Furthermore, VR100 rapeseed-based insulating oil and PFAE insulating oil are filtered and dried before use to meet the standard of GB 2536-2011.

[0011] Furthermore, the nanoparticles are nano-TiO2.

[0012] Furthermore, the particle size of nano-TiO2 is 5~10 nm, the morphology is anatase type, and the purity is 99.9%.

[0013] Furthermore, the mass concentration of KH550 surface modified nano-TiO2 in natural ester insulating oil is 0.03~0.15g / L.

[0014] Furthermore, the preparation method of KH550 surface-modified nanoparticles is: nano-TiO2, organic solvent, and silane coupling agent KH550 are mixed evenly, then heated to a preset temperature, condensed and refluxed for a preset time, filtered, and dried to obtain KH550 surface-modified nano-TiO2.

[0015] Furthermore, the organic solvent is one of ethanol, isopropanol and acetone.

[0016] The present application also provides a natural ester insulating oil modified by KH550 surface-modified nanoparticles, which is prepared by the above-mentioned preparation method and includes KH550 surface-modified nanoparticles and natural ester insulating oil.

[0017] In summary, the present application provides a method for preparing a natural ester insulating oil modified by KH550 surface modified nanoparticles, by mixing KH550 surface modified nanoparticles with a natural ester insulating oil mixed with VR100 rapeseed-based insulating oil and PFAE insulating oil, and finally obtaining a modified natural ester insulating oil. The natural ester insulating oil modified by KH550 surface modified nano-TiO2 exhibits excellent electrical properties. In the initial state, the modified natural ester insulating oil exhibits high breakdown voltage characteristics and has a stronger electric field carrying capacity; its low dielectric loss property can effectively reduce the amount of electric energy lost in the insulating oil. After entering the aging stage, the advantages of this insulating oil are still outstanding. The rate of decline of its breakdown voltage is greatly slowed down, and it can maintain a high value for a long period of time, continuously escorting the long-term insulation performance of the equipment; the growth rate of dielectric loss is extremely slow, which minimizes the risk of unstable operation caused by dielectric loss; the growth rate of acid value is effectively controlled, and the generation of acidic substances is strongly inhibited, thereby effectively delaying the aging process and extending the service life of the insulating oil. Compared with the prior art, the KH550 surface-modified nanoparticle-modified natural ester insulating oil involved in this application exhibits stronger aging resistance and lower dielectric loss, can accurately meet the diversified needs of electrical equipment, greatly extend the service life of the equipment, and provide a solid guarantee for the long-term stable operation and efficient maintenance of electrical equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0019] Figure 1 A schematic diagram of the synthesis of a modified natural ester insulating oil provided in an embodiment of the present application;

[0020] Figure 2 A schematic diagram of the structure of KH550 provided in the embodiment of the present application;

[0021] Figure 3 Transmission electron microscope images of nano-TiO2 (left) and KH550 surface-modified nano-TiO2 (right) provided in the examples of this application;

[0022] Figure 4 A schematic diagram of the breakdown voltage variation of the insulating oil provided in Examples 1 to 5 and Comparative Examples 1 to 6 of the present application;

[0023] Figure 5A schematic diagram of dielectric loss changes of insulating oils provided in Examples 1 to 5 and Comparative Examples 1 to 6 of the present application;

[0024] Figure 6 A schematic diagram of the change in volume resistivity of insulating oil provided in Examples 1 to 5 and Comparative Examples 1 to 6 of the present application;

[0025] Figure 7 A schematic diagram of the change in kinematic viscosity of insulating oil provided in Examples 1 to 5 and Comparative Examples 1 to 6 of the present application;

[0026] Figure 8 A schematic diagram of the change in breakdown voltage of insulating oil during aging provided in Example 1 and Comparative Example 6 of the present application;

[0027] Fig. 9 A schematic diagram of changes in the acid value of insulating oil during aging provided in Example 1 and Comparative Example 6 of the present application;

[0028] Fig.10 Schematic diagram of the change in dielectric loss of insulating oil during the aging process provided in Example 1 and Comparative Example 6 of the present application. DETAILED DESCRIPTION

[0029] The technical solutions of the embodiments of the present application will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the specification of the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection requested by the present application.

[0030] Among them, all raw materials of the present invention have no particular restrictions on their sources, and can be purchased on the market or prepared according to conventional methods known to those skilled in the art. Details of some raw materials used in the present invention are as follows:

[0031] Silane coupling agent KH550 is γ-aminopropyltriethoxysilane, its structural formula is shown in Figure 2 ;

[0032] VR100 rapeseed-based insulating oil, rapeseed vegetable insulating oil;

[0033] PFAE insulating oil is palm oil fatty acid ester insulating oil.

[0034] The embodiment of the present invention provides a method for preparing natural ester insulating oil modified by KH550 surface-modified nanoparticles, which is as follows:

[0035] Step S1, preparation of KH550 surface modified nanoparticles and base liquid:

[0036] Preparation of KH550 surface-modified nanoparticles: The nanoparticles, organic solvent, and silane coupling agent KH550 are mixed uniformly, then heated to a preset temperature, condensed and refluxed for a preset time, filtered, and dried to obtain KH550 surface-modified nanoparticles.

[0037] Preparation of base liquid: VR100 rapeseed-based insulating oil and PFAE insulating oil are mixed evenly to obtain base liquid;

[0038] Step S2, mixing the KH550 surface modified nanoparticles and the base liquid evenly, and drying to obtain modified natural ester insulating oil.

[0039] It should be noted that the introduction of organic functional groups on the surface of nanoparticles by silanization with the help of surface modification technology can effectively enhance the compatibility of nanoparticles with insulating oil and improve the stability of modified natural ester insulating oil. The specific reaction mechanism is: amino silane hydrolyzes and reacts with the hydroxyl groups on the surface of oxidized nanoparticles (such as nano-TiO2) to generate metal oxygen single bonds (such as TiO single bonds), that is, amino silane and nanoparticles are combined by chemical bonds, not simply physical adsorption. The organic groups introduced by the silanization of the surface of nanoparticles can significantly optimize the lipophilicity of nanoparticles, ensuring that they can be evenly dispersed in natural ester insulating oil; at the same time, the hydroxyl groups on the surface of nanoparticles after surface modification are significantly reduced, the adsorption between nanoparticles is weakened, and the possibility of agglomeration is reduced, further improving the long-term dispersion stability of nano-TiO2 modified natural ester insulating oil; also due to the introduction of KH550 surface modified nanoparticles, the interface thickness of nano-TiO2 and insulating oil increases after surface modification, and the effective contact area increases, resulting in a decrease in thermal resistance, thereby effectively improving the electrical and thermal conductivity of natural ester insulating oil.

[0040] In some embodiments, the mass ratio of VR100 rapeseed-based insulating oil to PFAE insulating oil is 4:1.

[0041] It should be noted that PFAE insulating oil exhibits a low viscosity characteristic. By mixing VR100 rapeseed-based insulating oil with PFAE insulating oil, a low-viscosity natural ester insulating oil can be prepared. Experiments have shown that when the mass ratio of VR100 rapeseed-based insulating oil to PFAE insulating oil reaches 4:1, the kinematic viscosity of the prepared natural ester insulating oil is at the lowest value, showing excellent fluidity, which has a significant promoting effect on improving the convective heat transfer efficiency inside the transformer.

[0042] Preferably, VR100 rapeseed-based insulating oil and PFAE insulating oil are filtered and dried before use to meet the standard of GB2536-2011.

[0043] It should be noted that filtering the insulating oil before use can effectively remove impurities, prevent the insulation performance from being reduced and the equipment from being worn due to the presence of impurity particles; while drying can remove moisture from the insulating oil, avoiding the deterioration of insulation performance, equipment failure and corrosion caused by moisture, thereby ensuring that the insulating oil plays its due key roles in insulation, heat dissipation, etc. in electrical equipment, maintaining the normal and stable operation of the equipment and extending the service life of the equipment.

[0044] In some embodiments, the nanoparticles are nano-TiO2.

[0045] It should be noted that when nano-TiO2 is selected as the nanoparticle, the amino group on KH550 reacts with the titanium hydroxyl group on the surface of nano-TiO2 through hydrolysis to generate a titanium oxygen single bond. The formation of this chemical bond allows KH550 to be branched to the surface of nano-TiO2, effectively improving the lipophilicity of nano-TiO2 and enhancing its dispersibility in insulating oil. Secondly, the amino group can change the electrostatic potential on the surface of nanoparticles, allowing nano-TiO2 to adsorb more charged particles, ultimately increasing the breakdown voltage of insulating oil.

[0046] More preferably, the particle size of nano-TiO2 is 5-10 nm, the morphology is anatase type, and the purity is 99.9%.

[0047] In some embodiments, the mass concentration of KH550 surface modified nano-TiO2 in natural ester insulating oil is 0.03-0.15 g / L.

[0048] In some embodiments, the preparation method of KH550 surface-modified nanoparticles is: nano-TiO2, organic solvent, and silane coupling agent KH550 are mixed evenly, then heated to a preset temperature, condensed and refluxed for a preset time, filtered, and dried to obtain KH550 surface-modified nano-TiO2.

[0049] Preferably, the organic solvent is one of ethanol, isopropanol and acetone.

[0050] The applicant further provides the following reference specific embodiments to describe the present invention. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0051] Example 1

[0052] See also Figure 1 This embodiment provides a method for preparing natural ester insulating oil modified by KH550 surface-modified nanoparticles, and the specific steps are as follows:

[0053] Step S1, preparation of KH550 surface-modified nano-TiO2 and base liquid:

[0054] Preparation of KH550 surface modified nano-TiO2: Place nano-TiO2 in a vacuum drying oven and dry it for 6 hours at a temperature of 90°C and a pressure of 50Pa. Pour the dried nano-TiO2 powder and 500mL of ethanol solution into a three-necked flask with a condenser, stir evenly, and then add the silane coupling agent KH550 (see Figure 2 ), heated to 70°C, condensed and refluxed for 3 hours, filtered and dried to obtain KH550 surface-modified nano-TiO2, see Figure 3 (Picture right);

[0055] Preparation of base liquid: VR100 rapeseed-based insulating oil and PFAE insulating oil were mixed in a mass ratio of 4:1, and stirred at a speed of 1200 r / min for 30 min to obtain the base liquid;

[0056] Step S2, KH550 surface modified nano-TiO2 and base liquid are placed in an ultrasonic disperser, ultrasonicated at an ultrasonic power of 960 W for 30 min, and placed in a vacuum drying oven after the ultrasonication, and dried at a pressure of 50 Pa and a temperature of 90°C for 48 hours to obtain insulating oil.

[0057] In this embodiment, the mass concentration of KH550 surface-modified nano-TiO2 is 0.03 g / L. A control group of KH550 surface-modified nano-TiO2 with a mass concentration of 0 g / L is also provided.

[0058] Embodiment 2~5

[0059] The difference from Example 1 is that the mass concentrations of KH550 surface-modified nano-TiO2 are different, namely 0.06 g / L, 0.09 g / L, 0.12 g / L, and 0.15 g / L, respectively.

[0060] Comparative Examples 1 to 5

[0061] The difference from Example 1 is that nano-TiO2 is used to replace KH550 surface-modified nano-TiO2, and the mass concentrations of nano-TiO2 in Comparative Examples 1 to 5 are 0.06 g / L, 0.09 g / L, 0.12 g / L, and 0.15 g / L, respectively.

[0062] Comparative Example 6

[0063] The difference from Example 1 is that KH550 surface-modified nano-TiO2 is not added, and the natural ester insulating oil is a mixture of VR100 rapeseed-based insulating oil and PFAE insulating oil in a mass ratio of 4:1.

[0064] The insulating oils prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were subjected to electrical performance tests, and the test items included breakdown voltage, dielectric loss, and volume resistivity. The test methods and results are as follows:

[0065] Test 1: Breakdown voltage test

[0066] According to the standard GB / T507-2002, the insulating oil prepared in the embodiment and the comparative example was tested for power frequency breakdown voltage using an intelligent withstand voltage test device under laboratory conditions. Before testing the breakdown voltage, the moisture content of each insulating oil was tested using a Karl Fischer moisture meter to ensure that the moisture content of the insulating oil after drying was ≤12 mg / L. The oil cup and the test electrode were rinsed with the insulating oil to be tested, and 300 mL of the prepared insulating oil was injected to ensure that the oil sample completely immersed the electrode. After the initial standing for 10 minutes, the boost program was started, and the boost rate was set to 2 kV / s. The breakdown operation was performed every 5 minutes, and the breakdown process was repeated 6 times in total, and the average value was taken as the final breakdown voltage value. When the insulating oil breaks down, a discharge occurs inside the oil sample, showing a significant electric spark or arc, and the voltage recorded at this moment is the breakdown voltage. After the breakdown, the oil molecules will form obvious black carbonization marks, accompanied by bubble generation. The oil cup used in the test is made of plexiglass, and the test electrode is a brass spherical cap electrode with a radius of 12.5 mm, and the electrode gap is set to 2.5 mm. Compared with the flat electrode, the uneven electric field generated by the spherical cap electrode has a higher field strength and a relatively concentrated distribution, which is more in line with the actual application scenario of insulating oil.

[0067] Test 2~3: Dielectric loss and volume resistivity test

[0068] Dielectric loss factor and volume resistivity are important parameters for characterizing the dielectric properties of insulating oil. Dielectric loss factor is the dielectric loss tangent (tanδ). According to the standard GB / T5654-2007, the DTLC type fully automatic dielectric loss and resistivity tester was used to measure the dielectric loss factor and volume resistivity of the sample at 90 °C. In the specific test process, a three-pole structure oil cup was used with an electrode distance of 2 mm. The frequency of the AC voltage was 55 Hz, the amplitude was 2 kV, and the DC voltage was 500 V.

[0069] Test 4: Kinematic viscosity test

[0070] The present application adopts the rotational viscometer method to measure the kinematic viscosity of the insulating oil.

[0071] In this application, the relevant test results of Examples 1 to 5 and Comparative Examples 1 to 5 are detailed in Figures 4 to 6 , in the figure, “KH-O” represents Examples 1 to 5, and “NA-O” represents Comparative Examples 1 to 5.

[0072] according to Figure 4It can be seen from the breakdown voltage test results presented that the breakdown voltage corresponding to Examples 1 to 5 is generally higher than the breakdown voltage values ​​of Comparative Examples 1 to 5. This phenomenon fully demonstrates that the modified natural ester insulating oil prepared by surface-modified nano-TiO2 of KH550 exhibits more excellent voltage breakdown characteristics. It is particularly noteworthy that when the mass concentration of surface-modified nano-TiO2 of KH550 reaches 0.03 g / L, the breakdown voltage that the modified natural ester insulating oil can carry reaches the highest value. Based on the data obtained, it can be further inferred that in the system represented by "KH-O", the surface-modified nanoparticles of KH550 have better dispersibility. It is precisely because of this good dispersibility that nano-TiO2 is not easy to agglomerate in natural ester, thereby avoiding the formation of conductive bridges due to agglomeration, so the corresponding breakdown voltage is improved, which ensures the insulation performance of the insulating oil under high voltage environment.

[0073] Figure 5 The relevant results of the dielectric loss test are shown. It can be clearly seen from the figure that the dielectric loss rates corresponding to Examples 1 to 5 are generally lower than the dielectric loss rates of Comparative Examples 1 to 5. This result means that the modified natural ester insulating oil with KH550 surface-modified nano-TiO2 exhibits more outstanding durability. Especially when the mass concentration of KH550 surface-modified nano-TiO2 is at a specific value of 0.03 g / L, the durability of the modified natural ester insulating oil reaches the strongest state, which can better maintain its stable performance and reduce the performance degradation caused by dielectric loss during long-term use.

[0074] Figure 6 The relevant results of volume resistivity are shown. It can be clearly seen from the figure that the volume resistivity corresponding to Examples 1 to 5 is lower than that of Comparative Examples 1 to 5 as a whole. This result means that the modified natural ester insulating oil with KH550 surface modified with nano-TiO2 exhibits lower resistance characteristics. Especially when the mass concentration of KH550 surface modified with nano-TiO2 is at a specific value of 0.03 g / L, the volume resistivity of the modified natural ester insulating oil is the lowest. The above data show that the volume resistivity of the modified natural ester insulating oil with KH550 surface modified with nano-TiO2 is significantly reduced. This feature is conducive to the transmission of current and the conduction and dissipation of heat, avoiding the phenomenon of overheating and aging of insulating oil caused by excessive accumulation of heat, and greatly extending the service life of insulating oil.

[0075] Figure 7The results of the kinematic viscosity measurements are clearly presented. It can be seen from the data in the figure that the kinematic viscosity data corresponding to Examples 1 to 5 are slightly lower than those of Comparative Examples 1 to 5. This phenomenon strongly indicates that nano-TiO2 surface-modified with KH550 can reduce the degree of agglomeration of nanoparticles in insulating oil and improve the compatibility and stability between nanoparticles and insulating oil. In a 30-day standing experiment, it was found by comparison that the rate of change of the KH-O transmittance was less than the rate of change of the NA-O transmittance. This result more strongly proves that KH550 has good long-term dispersion stability in insulating oil, that is, it can better maintain its own dispersion state in insulating oil during long-term standing, and is not prone to agglomeration, sedimentation and other performance-affecting situations, thereby providing a strong guarantee for the long-term stable use of the modified natural ester insulating oil in practical applications.

[0076] In summary, through the comparative analysis of various performances, it is clear that the modified natural ester insulating oil with KH550 surface-modified nano-TiO2 is far superior to the natural ester insulating oil without silane coupling agent modification and only with nano-TiO2 added. It is particularly noteworthy that when the mass concentration of KH550 surface-modified nano-TiO2 reaches 0.03 g / L, the modified natural ester insulating oil shows outstanding advantages in multiple key performance indicators such as breakdown voltage, dielectric loss, volume resistivity and long-term dispersion stability, and has good application prospects, which can provide strong support for improving the use efficiency of insulating oil in electrical equipment.

[0077] Test 5: Aging resistance test

[0078] The insulating oils prepared in Example 1 and Comparative Example 6 were subjected to an aging test for 56 days, and the breakdown voltage, acid value, and dielectric loss during the aging process were tested to characterize their aging performance, wherein NH-O represents Example 1, and PU-O represents Comparative Example 6. The results are shown in Figures 8 and 9 .

[0079] Figure 8 Figure 2 is the breakdown voltage test result of the aging stage. It can be seen from the figure that the breakdown voltage of Example 1 is generally higher than that of Comparative Example 6 during the entire test cycle. Specifically, at the critical time point of the 56th day of aging, the breakdown voltage of Example 1 is as high as 70.2 kV, while that of Comparative Example 6 is only 40.1 kV. This data comparison strongly proves that the modified natural ester insulating oil with KH550 surface modified with nano-TiO2 has stronger aging resistance. During the aging process, its physical and chemical properties show a high degree of stability and no significant changes occur, so that it can maintain a high insulation performance for a long time, effectively ensuring the safe and stable operation of electrical equipment under aging conditions.

[0080] Fig. 9The acid value test results of the aging stage are shown in the figure. It can be seen from the figure that the acid values ​​of Examples 1 to 5 are generally lower than those of Comparative Examples 1 to 5. This phenomenon shows that the modified natural ester insulating oil with KH550 surface modified with nano-TiO2 has significant advantages in aging resistance. During the aging period, the stability of its physical and chemical properties is reflected, and the acid value shows a slightly increasing trend with the aging time, rather than a sharp increase, which shows that the modified natural ester insulating oil can effectively inhibit the generation of acidic substances, slow down the negative impact of the accumulation of acidic substances on the performance of insulating oil, and thus maintain its stable performance during the aging process.

[0081] Fig.10 The dielectric loss test results of the aging stage can be seen from the figure that the dielectric loss rate of Example 1 is generally lower than that of Comparative Example 6. This shows that the modified natural ester insulating oil with KH550 surface modified with nano-TiO2 has stronger durability. Especially when the mass concentration of KH550 surface modified with nano-TiO2 is 0.03 g / L, the durability reaches the strongest state. During the aging process, the dielectric loss rate shows a slight upward trend with time, but the overall increase is small. In contrast, the dielectric loss of the insulating oil not modified with KH550 increases more significantly, further highlighting the important role of KH550 modification in improving the durability of insulating oil.

[0082] In summary, during the entire aging process, through a comprehensive comparison of various performance indicators, it can be found that compared with Comparative Example 6, Example 1 exhibits many advantages. Its breakdown voltage always maintains a large value, and the rate of decline is slower; the acid value and dielectric loss are smaller, and the growth rate is also more moderate. These results fully demonstrate that KH550 surface-modified nano-TiO2 can effectively slow down the aging process of natural ester insulating oil. Its mechanism of action is to inhibit the generation of acidic substances and moisture in the oil. In this way, it is beneficial to improve the thermal stability of natural ester insulating oil, so that natural ester insulating oil can better maintain its electrical performance and physical and chemical properties during long-term use, extend its service life in electrical equipment, and provide reliable insulation protection for the long-term stable operation of electrical equipment.

[0083] The above are only preferred embodiments of the present application and are not intended to limit the present invention. Although the present application has been described in detail with reference to the examples, those skilled in the art can still modify the technical solutions recorded in the aforementioned examples or make equivalent substitutions for some of the technical features therein. However, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing natural ester insulating oil modified by KH550 surface-modified nanoparticles, characterized in that: The KH550 surface modified nanoparticles are uniformly mixed with natural ester insulating oil to obtain modified natural ester insulating oil.

2. The method for preparing the KH550 surface-modified nanoparticle-modified natural ester insulating oil according to claim 1, characterized in that: The natural ester insulating oil includes VR100 rapeseed-based insulating oil and PFAE insulating oil.

3. The method for preparing the KH550 surface-modified nanoparticle-modified natural ester insulating oil according to any one of claims 1 or 2, characterized in that: The natural ester insulating oil includes VR100 rapeseed-based insulating oil and PFAE insulating oil, and the mass ratio of the VR100 rapeseed-based insulating oil to the PFAE insulating oil is 4:

1.

4. The method for preparing the KH550 surface-modified nanoparticle-modified natural ester insulating oil according to claim 2, characterized in that: The VR100 rapeseed-based insulating oil and the PFAE insulating oil are filtered and dried before use to meet the standard of GB 2536-2011.

5. The method for preparing the KH550 surface-modified nanoparticle-modified natural ester insulating oil according to claim 4, characterized in that: The nanoparticles are nano-TiO2.

6. The method for preparing the KH550 surface-modified nanoparticle-modified natural ester insulating oil according to claim 5, characterized in that: The particle size of the nano-TiO2 is 5-10 nm, the morphology is anatase type, and the purity is 99.9%.

7. The method for preparing the KH550 surface-modified nanoparticle-modified natural ester insulating oil according to claim 1, characterized in that: The mass concentration of the KH550 surface-modified nano-TiO2 in the natural ester insulating oil is 0.03-0.15 g / L.

8. The method for preparing the KH550 surface-modified nanoparticle-modified natural ester insulating oil according to claim 1, characterized in that: The preparation method of the KH550 surface-modified nanoparticles is as follows: nanoparticles, an organic solvent, and a silane coupling agent KH550 are uniformly mixed, then heated to a preset temperature, condensed and refluxed for a preset time, filtered, and dried to obtain KH550 surface-modified nanoparticles.

9. The method for preparing the KH550 surface-modified nanoparticle-modified natural ester insulating oil according to claim 8, characterized in that: The organic solvent is one of ethanol, isopropanol and acetone.

10. A natural ester insulating oil modified by KH550 surface-modified nanoparticles, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9, comprising KH550 surface-modified nanoparticles and natural ester insulating oil.

Citation Information

Patent Citations

  • Preparation method of high-volume resistivity palm insulating oil modified by nano magnesium oxide

    CN113604269A

  • High-stability natural ester insulating oil as well as preparation method and application thereof

    CN117887505A